Monetary policy uncertainty in China. (February 2021) - Chen, Hongyi; Tillmann, Peter
Highlights: Study monetary policy uncertainty in China. Uncertainty is measured from international newspapers. Uncertainty shock has strong effects on China and other Asian economies. Abstract: We propose a new measure of uncertainty about the monetary policy of the People's Bank of China (PBOC). The uncertainty index is extracted from the reporting about the PBOC's monetary policy in international newspapers. A shock to Chinese monetary policy uncertainty has significant effects on economic activity in mainland China. An increase in monetary policy uncertainty leads to a strong fall in investment, GDP and prices. We also show that a monetary policy uncertainty shock originating in mainland China has strong spillover effects on other Asian economies, leading to a fall in asset prices and GDP. An increase in reporting about uncertainty in international newspapers leads to a drop in stock prices throughout the region. Hence, uncertainty about the PBOC's monetary policy is an additional channel of transmission that coexists with the transmission of PBOC monetary policy itself. Finally, we show that our index contains information over and above what is already incorporated in monetary policy uncertainty indices based on mainland newspapers.